'To Act upon one's Time …' From the impulse to resist to global political strategy. (March 2019) - Müller, Birgit
This article reflects on the possibilities for political action emerging out of quotidian engagements. Following controversies on the patenting of seeds in Canada and globally within the Committee for Food Security I explore what gave the impulse for political resistance in these different arenas. How did collective action emerge and how did it sustain itself? Three political concepts are important for understanding the political actions that I observed: Eigen-Sinn, empathy and strategy. These allowed me to follow and theorize political engagements. I first reflect on the potential to resist as a capacity of all human beings, because they have Eigen-Sinn: the capacity to attribute their own meanings to things, and act in their own self-interested way according to the meaning given. Self-interested action can only become political, however, when humans go beyond their strictly individual interests and empathize with others (humans and nonhumans), what Adorno described as getting into 'live contact with the warmth of things'. Finally, I discuss how collective action can become not only possible, but also effective, by building and defending a space for strategic action.